Technical efficiency of lumber recovery from high forest tree species in selected sawmills of Southwestern Nigeria (2011)
This study investigates the technical performance efficiency (TPE) of twenty seven sawmills purposely selected and grouped into three classes :small<500ft3/day, medium 501-1000ft3/day and large scale >1001ft3/day based on their production capacities. 243 logs obtained from 20 species of wood sourced from Southwestern Nigeria were examined in 27 selected sawmills using the variables such as wood species, log sizes, shapes and sawkerf, which have direct impact on waste generated from sawn logs and log conversion efficiency. Whereas 135 structured questionnaire was used to obtain information relating to experience of headrig operators, age of machine, number of machine used for sawing operation, hands involved in operation and effective duration of operation while a model multiple factor equation was adopted to determine the over all performance efficiency of the assessed sawmills. The average TPE in the small scale sawmills was 53.41%, medium scale sawmills with 58.79% had the highest performance efficiency while large scale sawmills with 41.94% had the least TPE. The average lumber recovery (%LR) was 53.69%, large-sized diameter logs had the highest %LR of 56.48 and small sized logs had 51.77%. Ondo State had the highest mean %LR of 56.15 followed by Lagos (53.09%) and lastly by Oyo State (51.71%). Variations in log diameter classes had significant influence on %LR, slab volume and dust volume at (p<0.05). Significant correlation also exist between log diameter class and LR (0.853**). Noticeable variation in %LR was observed among the various wood species, Ceiba pentandra had the highest mean lumber recovery %LR value of 58.21% while Nauclea diderichii had the least (47.89%). For appreciable reduction of wood-wastes generated in sawmills, greater use should be made of large sized logs, routine maintenance of machines especially the saw blades is necessary, effort should be made towards inclusion of wood mizer headrig that handles smaller sized los with minimal wastages and obsolete headrig need to be replaced promptly while cognate experience should be a major determinant in the appointment of headrig operators. To avoid genetic erosion, choice of species was left to saw millers’ discretion.